The Gemidiriya Program, Sri Lanka : Piloting the Community Assessment Process - Agarwal, Sanjay; Shah, Parmesh; Sirker, Karen (World Bank, Washington, DC, 2016)
The Gemidiriya program's long-term objective is to reduce rural poverty and promote sustainable and equitable rural development. The program aims at creating an environment that enables rural communities to improve their livelihoods and quality of life. It paves the way for rural communities to get together, organize formally, plan village development by themselves with 50 percent women participation, and to mobilize self-help and community contributions. The Gemidiriya focuses on building accountable and self-governing local institutions by: (i) devolving decision-making power and resources to community organizations; (ii) strengthening selected local governments that demonstrate responsiveness and accountability to rural communities; and (iii) working with federations of village organizations (VOs), the private sector, and non governmental organizations (NGOs) on economic empowerment to increase the size and diversity of livelihoods. This note summarizes the findings, processes, concerns, and lessons learned from the Sri Lanka pilot.